PENDAMPINGAN BIMBINGAN BELAJAR UNTUK MENUMBUHKAN MOTIVASI PADA SISWA DI TPQ NURUL WATHAN DESA TRIWUNGAN KABUPATEN PROBOLINGGO - Juhairiyah Juhairiyah; Purwaning Putri; Mariatul Kiftiah Wasilah; Yahmun Yahmun; Susandi Susandi; Ike Dian Puspita Sari (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2023)
Community Service which is one of the ways or efforts to implement the tri dharma of higher education. This is done with the aim of fostering student motivation and interest in the learning provided by the teacher. The learning assistance methods that are applied to students at TPQ Wathan, include; students and students carry out learning and teaching procedures directly. This tutoring assistance is carried out at TPQ Wathan, Triwungan Village, Probolinggo Regency, the material provided and taught by the teacher in tutoring assistance is desired by students The target object in the tutoring assistance research is students at the elementary level grades 1-6.